2019
DOI: 10.3389/fpsyg.2019.02024
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions Can Be Improved in Preschoolers Through Systematic Playing in Educational Settings: Evidence From a Longitudinal Study

Abstract: This study aimed to test the impact of play on the development of executive functions (EFs) in preschoolers. Thirty-two games were designed to be collectively played in groups by 70 children, in their regular classes. The games were specifically designed to promote the development of the three components of EFs: inhibition (behavioral or cognitive), working memory, and cognitive flexibility. The games focused on each function were of three types: playground games, expression games, and classroom games. Sixty 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 60 publications
0
24
0
6
Order By: Relevance
“…Second, some researchers believe that the components of EF are independent of each other, including two-factor models (Monette et al, 2015) and three-factor model (Espy et al, 2004;Miller and Best, 2010;Hughes, 2011;Skogan et al, 2015). According to previous researchs on the EF training of preschool children (e.g., Lakes and Hoyt, 2004;Schonert-Reichl et al, 2015;Rosas et al, 2019;Shen et al, 2019), researchers mainly focus on three basic components.…”
Section: Executive Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, some researchers believe that the components of EF are independent of each other, including two-factor models (Monette et al, 2015) and three-factor model (Espy et al, 2004;Miller and Best, 2010;Hughes, 2011;Skogan et al, 2015). According to previous researchs on the EF training of preschool children (e.g., Lakes and Hoyt, 2004;Schonert-Reichl et al, 2015;Rosas et al, 2019;Shen et al, 2019), researchers mainly focus on three basic components.…”
Section: Executive Functionmentioning
confidence: 99%
“…Sports training can be game training, aerobic training, martial arts training, and so on. Rosas et al (2019) specially designed 32 games to promote the development of EF in which 35 children were trained for 3 months. The results showed that compared with the control group, the EF of children in the training group was significantly improved.…”
Section: Sports Trainingmentioning
confidence: 99%
“…Cognitive Outcomes: intelligence, processing speed, and executive function [ 2 , 27 , 53 , 54 , 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Executive function refers to the top-down neurocognitive processes involved in the conscious, goal-directed control of thought, action, and emotions. Effective executive function and functional working memory are both reliant upon the integrity of neural networks involving the prefrontal cortex (PFC), the anterior cingulate cortex, and other regions [11][12][13], and they are required for keeping the information in mind, attending selectively, ignoring distractions, and solving problems flexibly [14].…”
Section: Introductionmentioning
confidence: 99%